2020
DOI: 10.3389/fbioe.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Non-cellular Bioactive Glass-Containing Scaffolds on Osteogenesis and Angiogenesis in in vivo Animal Bone Defect Models

Abstract: The use of bone scaffolds to replace injured or diseased bone has many advantages over the currently used autologous and allogeneic options in clinical practice. This systematic review evaluates the current evidence for non-cellular scaffolds containing bioactive glass on osteogenesis and angiogenesis in animal bone defect models. Studies that reported results of osteogenesis via micro-CT and results of angiogenesis via Microfil perfusion or immunohistochemistry were included in the review. A literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Silicon has also been considered a potent element that promotes angiogenesis at therapeutic doses [ 35 ]. Release of silicic acid is considered to be the major factor in promoting osteogenesis of bioceramic materials [ 36 ]. Silicic acid molecules that enter cells act as signals for upregulation of genes that generate cell cycle regulator proteins and growth factors [ 16 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silicon has also been considered a potent element that promotes angiogenesis at therapeutic doses [ 35 ]. Release of silicic acid is considered to be the major factor in promoting osteogenesis of bioceramic materials [ 36 ]. Silicic acid molecules that enter cells act as signals for upregulation of genes that generate cell cycle regulator proteins and growth factors [ 16 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…One leading obstacle for most tissue-engineered scaffolds is the lack of sufficient vascularization within the scaffold [ 6 ]. As slow ingrowth of the host's vasculature into the center of bone grafts hinders further bone consolidation [ 7 ], some have concluded that neovascularization is vital to bone regeneration [ 8 ]. New strategies are needed to overcome this roadblock and effectively achieve vascularized tissue-engineered bone grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Heterotopic ossification refers to the formation of pathological bone in soft tissue and can occur with soft tissue injury, including tendon injury. 48 Given that BG has been reported to promote osteogenesis, 49 it may, therefore, increase the risk of heterotopic ossification. To assess whether BG/SA hydrogel treatment induced heterotopic ossification, we performed IHC staining of RUNX2 and OCN (early and late osteolineage markers, indicating mineralization sites).…”
Section: Resultsmentioning
confidence: 99%